WEBSITE-BASED INVENTORY CONTROL APPLICATION USING THE METHOD ECONOMIC ORDER QUANTITY AND ROP REORDER POINTS - Suriati Sitepu; Victor Tarigan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
UD.Gokkon Tani is a family-owned business in Balimbingan, Tanah Jawa District, Simalungun Regency. The problems that occur at UD.Gokkon Tani start from the process of recording data on goods sold, the process of recording purchases of goods and the process of recording stock of goods. The impact of this manual process is that problems often occur in handling inventory such as errors in determining the amount of inventory. which will be ordered to suppliers, there is often an out of stock of goods, there is often an excessive supply of goods resulting in a buildup of goods in the warehouse. To prevent this from happening again, the Economic Order Quantity and Reorder Point methods are used to minimize calculation errors in carrying out inventory and the process of saving capital in the costs of storing and shipping goods. Using the PHP programming language can produce a website application that can calculate EOQ and ROP and the results of these two methods can save Total Inventory Cost compared to company calculations so far